PRAKTIK NIKAH TANPA PACARAN DI LINGKUNGAN ANGGOTA PELOPOR PARTAI KEADILAN SEJAHTERA (PKS) DAN PENGARUHNYA TERHADAP HARMONI RUMAH TANGGA - Muhannan Mu'min Mushonnaf (Universitas Islam Negeri (UIN) Mataram, 2022)
In Indonesia, one of the communities that practice the concept of marriage without dating is the institution or congregation of the Prosperous Justice Party (PKS). PKS in practice, is often identified with the grouping of their cadres in choosing a mate. In its application, there is no term dating between men and women, but to get to a marriage is called ta'aruf. Furthermore, what is interesting to study is the extent to which the process or practice of marriage without dating affects the household harmony of the PKS pioneer cadres. In other words, the practice of marriage in the ta'aruf way, without a personal relationship between the prospective bride and groom, will affect the quality of the marriage of the PKS members. This research was conducted using a qualitative approach. Qualitative research aims to obtain an authentic understanding of people, as perceived by the people concerned. Qualitative methods are used to reveal the nature of one's experience with certain phenomena. In addition, qualitative methods can also be used to reveal something in batik that is a little and unknown phenomenon. This method can also be used to gain insight into something little known. The focus of this research is the harmony of individual marriages, in this case the pioneer members of the Prosperous Justice Party (PKS) of East Lombok Regency, who married without dating. The conclusion from the discussion above is that there is a practice of marriage without dating among the pioneer members of the PKS in East Lombok Regency. The pioneer members of the PKS East Lombok Regency married through an institution owned by PKS, namely the Marriage Institution, which aimed to carry out the ta'aruf process as wasilah for the meeting of prospective brides and grooms. This affects the household harmony of PKS members. In general, interviews conducted with PKS members and the community who interact with PKS members show that PKS cadre households are harmonious households.